Focal points, beliefs, and distributional preferences: An experimental analysis - Jo\~ao V. Ferreira; Nobuyuki Hanaki; Benoît Tarroux (Osaka University, Institute of Social and Economic Research (ISER), 2025)
This paper experimentally examines the interplay between focal points, beliefs, and distributional preferences. Contrary to common wisdom, there is no detectable evidence that equal splits act as salient focal points in distributional voting contexts. Participants mispredict others' preferences: they overestimate egalitarianism when Pareto efficient options are available and underestimate it when efficiency gains come at others' expense. There is a clear correlation between individuals' preferences and beliefs (false-consensus bias), and participants are more egalitarian when they perceive a low probability of being pivotal (cheap fairman talk). These findings challenge assumptions about focal points and highlight belief-driven behavior in distributional settings.
Keywords: C9; D3; D63; D7; D9; 330; Distributional preferences; Focal Points; Equal split; Belief elicitation; False-consensus bias